Little rot eaudiobook A novel. - Emezi, Akwaeke (Books on Tape, 2024)
“A masterwork…mesmerizing…We come away troubled, unsettled — and in some subtle way changed.” – The New York Times "The perfect steamy read for those hot summer nights." – People A thrilling new novel from the bestselling, award-winning, visionary Akwaeke Emezi   One weekend. The elite underbelly of a Nigerian city. A party that goes awry. A tangled web of sex and lies and corruption that leaves no one unscathed. Aima and Kalu are a longtime couple who have just split. When Kalu, reeling from the breakup, visits an exclusive sex party hosted by his best friend, Ahmed, he makes a decision that will plunge them all into chaos, brutally and suddenly upending their lives. Ola and Souraya, two Nigerian sex workers visiting from Kuala Lumpur, collide into the scene just as everything goes to hell. Sucked into the city’s corrupt and glittering underworld, they’re all looking for a way out, fueled by a desperate need to escape the dangerous threat that looms over them.